The Influence of Promotions, Service Quality and Trust on Customers' Interest in Saving at BSI KCP Jambi Rimbo Bujang 1 - Wuri Suhasti; Rina Istiqomawati; Andriyani Widiyastuti; Destia Dewi (International Journal of Scientific Multidisciplinary Research, 2024)
BSI KCP Jambi Rimbo Bujang 1 is the first sub-branch office established in Tebo Regency, Jambi. BSI is a combination of BNI Syariah, BRI Syariah and Mandiri Syariah since 2 years ago. The Bank Syariah Indonesia office in Tebo Regency serves BSI Bank customers to create new accounts, cash deposits, withdraw savings funds, check balances, apply for loans/credit and services, BSI ATMs for other BSI products. During its development, the growth in the number of customers was very slow even though many promotions had been carried out and the quality of service was also very good. This research aims to determine the influence of promotion, service quality and trust on interest in saving at BSI KCP Jambi Rimbo Bujang 1. The research method used is quantitative research. The data analysis technique uses multiple regression analysis with the t test and F test. Data was obtained by distributing questionnaires to 150 respondents using the Purposive Sampling Technique. The results of this research show that in part the promotion variable has a significant influence on interest in saving as evidenced by a value of 0.006 < 0.05 with a t value of 2.803 > t table 1.757, the service quality variable has a significant influence on interest in saving as evidenced by a significant value of 0.009 < 0, 05 with a tcount value of 2.663 > ttable 1.757, and the trust variable also has a significant influence on interest in saving as evidenced by a significant value of 0.001 < 0.05 with a tcount value of 4.299 > ttable 1.757. Simultaneously (at the same time) promotion, service quality and trust have an influence on interest in saving as shown by the value of Fcount > Ftable (56.112 > 2.67) with a significant value of 0.001 < 0.005